2018
DOI: 10.1016/j.jtho.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Survival Comparison in Patients with Stage IV Lung Cancer in Academic versus Community Centers in the United States

Abstract: Introduction: Although metastatic NSCLC is widely treated in both academic centers (ACs) and community-based centers (CCs), it is unclear whether outcomes are similar across both settings. A growing variety of chemotherapies and targeted agents for an increasingly histology-and molecularbased treatment strategy could provide an advantage to patients treated in ACs. Using the National Cancer Database, we investigated whether treatment at ACs was associated with a survival advantage in metastatic NSCLC. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The aforementioned study recommended that patients with N 0 stage should be eligible for surgical treatment and that surgery for patients with extensive lymph node metastases may not be beneficial (55). There are few studies investigating the prognosis of patients with stage IV NSCLC with adenocarcinoma and squamous carcinoma (56,57). A retrospective study of 148 Chinese patients with NSCLC revealed that non-lung adenocarcinoma was a prognostic risk factor in patients with NSCLC (57), consistent with the results obtained in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned study recommended that patients with N 0 stage should be eligible for surgical treatment and that surgery for patients with extensive lymph node metastases may not be beneficial (55). There are few studies investigating the prognosis of patients with stage IV NSCLC with adenocarcinoma and squamous carcinoma (56,57). A retrospective study of 148 Chinese patients with NSCLC revealed that non-lung adenocarcinoma was a prognostic risk factor in patients with NSCLC (57), consistent with the results obtained in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although blockade of the programmed death-1 receptor ligand 1 pathway is a powerful therapeutic strategy for NSCLC 30, this disease still has a dismal prognosis 31, 32, so genetic information that can be useful for lung cancer prognosis or prediction is essential. Our results reveal a significant correlation between NSCLC and clinical status in 695 Chinese Han patients; in 527 patients with NSCLC, those with Ang2 polymorphisms carrying the GT genotype at rs12674822 were 1.56-fold more likely to develop stage II, III or IV disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the cohort herein, survival of patients receiving vinorelbine as single-drug regimen compared well with current knowledge regarding the outcome of patients receiving more conventional chemotherapy for stage IV NSCLC. For instance, in a recent epidemiological study of the national cancer data base (NCDB), the authors investigated the two-year survival from date of diagnosis to death in 193,279 patients with metastatic NSCLC [19]. Two-year survival improved from 9.9% in 1998 to 14.6% in 2010.…”
Section: Discussionmentioning
confidence: 99%